Schistosoma japonicum Soluble Egg Antigen Protects Against Type 2 Diabetes in Leprdb/db Mice by Enhancing Regulatory T Cells and Th2 Cytokines - Tang, Chun-lian; Yu, Xiao-hong; Li, Yan; Zhang, Rong-hui; Xie, Jun; Liu, Zhi-ming (Frontiers in Immunology, 2019)
Type 2 diabetes is a metabolic disorder characterized by persistently elevated glucose levels. There is no effective treatment strategy for this condition, and it poses a massive economic burden globally. Schistosoma soluble egg antigen (SEA)-induced immunomodulatory mechanisms have been reported in the treatment of autoimmune disease. This study aimed to determine the ability of Schistosoma japonicum SEA to protect against type 2 diabetes in Leprdb/db mice and understand the associated mechanisms. The mice were divided into four groups: C57BL/6 (the normal group), SEA (C57BL/6 mice treated with SEA), Leprdb/db, and SEA and Leprdb/db co-treatment groups. The mice in the SEA and co-treatment groups were injected with 50 μg of SEA (twice a week for 6 weeks), and the same volume of PBS was used as control. Blood glucose, insulin, and HOMA-IR levels were measured in all mice, which were sacrificed 6 weeks after the last SEA administration. Flow cytometry was used to detect the percentages of regulatory T cells in splenocytes. ELISA was used to detect the levels of IFN-γ, IL-2, IL-4, and IL-5 in cell culture supernatants. Compared with the mice in the Leprdb/db group, the mice in the SEA+Leprdb/db group exhibited significantly reduced insulin resistance, as evidenced by the enhancement of wound healing. The frequency of spleen regulatory T cells increased significantly after SEA administration; meanwhile, the secretion of IL-4 and IL-5 in spleen cells was elevated. These results indicate that SEA can reduce insulin resistance and provide new targets for the treatment of type 2 diabetes. The potential mechanisms might be associated with increases in regulatory T cells and Th2 cytokines in Leprdb/db mice, which warrants further investigation.